Antibacterial and Antioxidant Activity of Nam-Nam Fruit Extract: Antibacterial activity of Nam-Nam fruit extract - Somsap, On-Anong; Piboonpol, Gornganok; Payanglee, Kolip; Daengrot, Charuwan (Princess of Naradhiwas University Journal, 2019)
Medicinal plant extract is recognized as anti-bacterial and antioxidant. This research aims to investigate the efficacy of Nam-Nam fruit extract to against bacterial and antioxidant activity. Anti-bacterial activity was determined by agar well diffusion method. The results showed that only Gram-positive bacteria susceptible to Nam-Nam fresh fruit juice and ethanol extract. Bacillus cereus ATCC11778 showed susceptibility to Nam-Nam-fresh fruit juice and ethanol extract with inhibition zone of 17 and 25 mm, respectively. Comparison the antibacterial activity between Nam-Nam fruit extract with gentamicin (10 ug) found that MRSA142 susceptible to Nam-Nam extract but resistance to gentamicin (10 ug). The MIC values of both extract of Nam-Nam fruit to against MRSA142 was 500 mg/ml. For the study of antioxidant activity was determined by using DPPH solution. The result showed antioxidant activity more than 50% inhibition at concentration of 71.21 mg/ml and 76 mg/ml, respectively. Moreover, the total flavonoids content in both of Nam-Nam fruit extract were 5.48 and 7.10 mg/ml, respectively.